Achievement of promising cryogenic magnetocaloric performances in La1-xPrxFe12B6 compounds. (30th November 2021) - Ma, Zhipan; Dong, Xiaoshi; Zhang, Zhenqian; Li, Lingwei
Abstract: The magnetic refrigeration (MR) utilizing magnetocaloric effect (MCE) has been recognized as an environmentally friendly and energy efficiency technology. Here we presented the magnetic properties and MCE in Pr-doped La1 -x Pr x Fe12 B6 ( x =0.05-0.2) itinerant-electron metamagnetic (IEM) compounds. A small amount of Pr doping La site can greatly improve the peak values in the magnetic entropy change Δ S M ( T ) curves, especially under relatively low magnetic field changes (Δ H ). Additionally, the peak temperature increases gradually and the magnetic hysteresis reduces gradually with increasing x . The observed MCE in present La1 -x Pr x Fe12 B6 compounds is related to its field-induced first-ordered IEM transition. The peak values of Δ S M for La1 -x Pr x Fe12 B6 compounds reach 13.4, 15.4, 12.5 and 13.0 J/(kg K) at T C ~58, 68, 72 and 89 K for x =0.05, 0.10, 0.15 and 0.2 under Δ H of 0-7 T, respectively. The corresponding relative cooling power values are 462.3, 480.7, 372.4 and 375.7 J/kg. The present La1 -x Pr x Fe12 B6 compounds could be good candidates for active MR application if the magnetic and thermal hysteresis can be further reduced. The present work indicates that the LaFe12 B6 -based material system could also exhibit promising magnetocaloric performances. Highlights: Magnetic and magnetocaloric properties in La1 -x Pr x Fe12 B6 are investigated. Promising cryogenic magnetocaloric performances have been observed. La1 -x Pr x Fe12 B6 compounds are considerable for magnetic refrigeration.